Placenta accreta spectrum. Current diagnostic issues - A. E. Volkov; M. A. Rymashevskiy; I. V. Andrusenko (Медицинский вестник Юга России, 2023)
In this review of the literature, the issues of diagnosis of abnormal attachment (ingrowth) of the placenta (PAS) are considered: ultrasound scanning (ultrasound), magnetic resonance imaging (MRI), the study of serum markers of the anomaly. A systematic literature search was conducted on the databases PudMed, Scopus and others. The issues of the evolution of views on the causes of this anomaly and its classifications are also discussed. It is noted that currently the main method of diagnosis of placenta accreta is ultrasound. Two-dimensional grayscale scanning in combination with color Doppler mapping (CDK) and three-dimensional echography with the option of energy Doppler is recommended. However, echography remains an absolutely "operator dependent" method, therefore, largely subjective, determined by the experience of a specialist in detecting this pathology with an instrument. MRI is recommended as a tool for assessing the depth of invasion in case of suspected placenta percreta and in the diagnosis of complex cases (placenta previa along the posterior wall of the uterus). Ultrasound and MRI have a very high diagnostic potential. It is generally considered that ultrasound is an inexpensive, widely available imaging method, recommended as a priority in the diagnosis of PAS. MRI does not play a primary role in the diagnosis of PAS, but it can be indispensable for detailing the topography of areas that are difficult to assess with ultrasound.